2013
DOI: 10.1016/j.jpainsymman.2012.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence Base for Oxygen for Chronic Refractory Breathlessness: Issues, Gaps, and a Future Work Plan

Abstract: Please note that any alterations made during the publishing process may not appear in this version."NOTICE: this is the authors' version of a work that was accepted for publication in the Journal of Pain and Symptom Management. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…Similarly, the majority of HCPs regarded oxygen as a universal remedy, a belief which stems from experience that it works ! Overuse and misunderstanding of oxygen by HCPs is common, although rationale appears elusive. It has been intimated previously that a culture may exist whereby oxygen is given automatically to patients who present as critically ill or dyspnoeic; this is the first time that this culture, underpinned by beliefs, misconceptions and myths, has been captured and reported as empirical data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the majority of HCPs regarded oxygen as a universal remedy, a belief which stems from experience that it works ! Overuse and misunderstanding of oxygen by HCPs is common, although rationale appears elusive. It has been intimated previously that a culture may exist whereby oxygen is given automatically to patients who present as critically ill or dyspnoeic; this is the first time that this culture, underpinned by beliefs, misconceptions and myths, has been captured and reported as empirical data.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there is no doubt that it's use to correct hypoxaemia is essential, there is a growing body of evidence suggesting that when too much oxygen is given, this may lead to adverse events and even death . Additionally, the use of oxygen to relieve dyspnoea is increasingly controversial, seemingly exacerbated by a lack of clear guidance and consensus . The publication of the first UK (United Kingdom) Emergency Oxygen Guidelines challenged established custom but, despite this initiative, audit suggests persistence of poor practices .…”
Section: Introductionmentioning
confidence: 99%
“…[3,40] It has been suggested that excellent communication is required to discuss difficult decisions [41]addressing a patient's fears of dyspnoea needs to be a key priority for HCPs, in addition to education regarding futility and dangers of oxygen.…”
Section: 'Sometimes the Family And The Patient Don't Want To Be Seen mentioning
confidence: 99%
“…125 Of the 13 studies reviewed, 2 showed a benefit when supplementing oxygen to breathless subjects. These 2 studies involved COPD patients, and the benefit of oxygen administration was small and limited to breathlessness as a result of exertional desaturation in one study.…”
Section: Breathlessnessmentioning
confidence: 99%